DESAIN PEMBELAJARAN BAHASA INGGRIS BERMUATAN MOTIVASI DAN KARAKTER - Irwandi, Irwandi (Pelita Bangsa Pelestari Pancasila, 2017)
It is important to think that all of the learning activities are tied closely to learners’ motivation and character building. Motivationincites or stimulates the learners to attain their purpose, and while, character is the measurement of people’s perceived manners and an overall evaluation of people’s inward and outward behavior. Without having high motivation, there is no a dynamics in the class. On the contarary, motivated learners are willing to work hard, focus their attention on the tasks, and may even promote collaborative learning and stimulate others in the classroom. Learning English does not mere focus on the mastery of language skills, but it has the dimension of character building. This paper is an attempt to propose a design of instruction for learning English languageon the dimension of motivation and character building. It mostly includes the concept of motivation, character, and the model of design of instruction for English class on motivation and character building based-orientation.